(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect of housing on haematological parameters of Nellore Jodipi lambs. Thirty weaned Nellore ram lambs of 3-4 months age were divided into three groups of ten each. The lambs in Group-I were housed with morum flooring and asbestos roofing with tree shade, while Group-II lambs were housed with morum flooring and asbestos roofing without tree shade and Group-III lambs were housed with elevated slatted flooring and galvalume roofing without tree shade. Temperature and humidity values were significantly (P<0.05) different among all the groups. Lower mean maximum temperature (°C) values were observed in group III (35.53±0.28) when compared to group I (36.22±0.27) and II (37.29±0.25) and the lower average maximum relative humidity (%) was 69.59±2.92 in group III followed by group II (69.88±2.94) and I (70.65±2.96). The mean haematological parameters like RBC, WBC, Hb, PCV were significantly (P<0.05) lower in group III (8.22±1.00×106/μl, 6.99±1.00×103/μl, 10.22±0.08 g/dl, 28.23±1.00 %) when compared to group I (9.66±1.00×106/μl, 9.01±1.00×103/μl, 10.85±0.08 g/dl, 31.27±1.00 %) and II (11.96±1.00×106/μl, 11.73±1.00×103/μl, 13.64±1.00 g/dl, 37.27±1.00%), respectively, whereas, other parameters like MCH, MCV, MCHC are significantly (P<0.05) higher in group III (11.52±1.00 pg, 34.92±1.00 fl, 36.57±1.00 g/dl) when compared to group I (10.23±1.00 pg, 31.85±1.00 fl, 34.02±1.00 g/dl) and II (8.92±1.00 pg, 28.05±1.00 fl, 32.15±1.00 g/dl), respectively. It was concluded that the housing system of elevated slatted flooring with galvalume roofing proved to be effective in controlling heat stress and maintaining normal hematological parameters for better growth performance of Nellore ram lambs..